From “Slaves of the Kitchen” to “Thanks to the Union”: Greek-American Hotel and Restaurant Workers during the Great Depression - Karpozilos, Kostis (Food & History, 2013)
Abstract This article explores the conditions of labour and the unionising activities of rank-and-file workers in hotels and restaurants during the Great Depression through the case of Greek-American culinary and service workers. More particularly it charts the correlation between class-oriented conceptualisations and the activities of the Greek-American Left, while it addresses the transformations of ethnicity within the boundaries of small ethnic enterprises. In this context, Greek-American workers do not represent an exceptional case, but offer a paradigm of the multiple ways ethnic organisation contributed to the development of labour unionism in the turbulent 1930s and the rise of a labour-capital regulation that substituted the preexisting chaotic conditions in the food industry.